CONSUMER SATISFACTION WITH THE LEVEL OF SERVICE QUALITY OF TELECOMMUNICATION COMPANIES IN UGANDA; A CASE STUDY OF AIRTEL UGANDA - Johnpaul Ssentongo Lwanga (Uganda Christain University, 2024)
This study investigates consumer satisfaction with the service quality of Airtel Uganda, a leading telecommunications company in Uganda. The research aims to evaluate the current level of consumer satisfaction, identify key factors influencing consumer perceptions, assess the relationship between various dimensions of service quality (such as reliability, responsiveness, assurance, and empathy), and provide actionable recommendations for enhancing service quality. The findings reveal a general dissatisfaction among Airtel Uganda's customers, primarily due to high tariffs, the perishability of internet bundles, frequent network disruptions, and inconsistent customer service. Factors such as network stability, transparent pricing, and customer service quality were identified as significant in shaping consumer perceptions of Airtel Uganda’s service quality. The study further explores how dimensions like reliability and responsiveness are critical in influencing overall customer satisfaction, with areas like assurance and empathy offering potential for improvement. Based on the findings, the study recommends a series of strategic initiatives for Airtel Uganda, including upgrading network infrastructure, simplifying pricing structures, enhancing customer service, and introducing innovative value-added services. Implementing these recommendations could lead to significant improvements in service quality and customer satisfaction, fostering greater customer loyalty in Uganda's competitive telecommunications market.